2011
DOI: 10.4018/jictrda.2011010102
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of E-Commerce in Developing Countries

Abstract: The growth of the Internet has opened up a vast arena, providing more opportunities for businesses, particularly small to medium-sized enterprises (SMEs) to sell their products and services to a global audience than they would have been able to afford to reach using the traditional methods. SMEs are extremely important to many countries and their contribution to economy cannot be over emphasized. Several researchers have studied the contribution of the Internet and highlight the importance of convenience, sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…This is the basis of trust that underpins e-commerce in the developed world. In Nigeria, legal and judicial institutions are underdeveloped, individual consumers and enterprises lack confidence and trust to engage on internet transactions (Lawrence and Usman, 2010). The authors affirmed that reluctance to adoption of e-commerce in developing countries could be traced to limitation on personal contact.…”
Section: Infrastructural Barriersmentioning
confidence: 85%
See 2 more Smart Citations
“…This is the basis of trust that underpins e-commerce in the developed world. In Nigeria, legal and judicial institutions are underdeveloped, individual consumers and enterprises lack confidence and trust to engage on internet transactions (Lawrence and Usman, 2010). The authors affirmed that reluctance to adoption of e-commerce in developing countries could be traced to limitation on personal contact.…”
Section: Infrastructural Barriersmentioning
confidence: 85%
“…Most developing countries are not prepared for e-commerce, due to lack of network infrastructure, especially among individual users and business people. E-commerce accomplishment depends heavily on a number of infrastructure technologies (Lawrence and Usman, 2010). Lawrence and Usman (2010) found that in most developing countries like Kenya, Nigeria and Togo that are embracing outdated telephone cords and unreliable extension wires, due to this may result to the low performance many providers of internet services encounter.…”
Section: Infrastructural Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the business is conducted through small enterprises and it is local. A typical company in developing country is a socio-economic entity and not just a pure economic one (Lawrence & Tar, 2010). Thus, some business traditions that make e-commerce work elsewhere -such as catalogue shopping -do not exist in the region.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Economics always play an important role in encouraging the use of technology in developing countries (Economic Commission for Africa, 1999). However, economic condition in developing countries is widely recognized as a major hindrance for e-commerce adoption (Lawrence & Tar, 2010). To measure the impact of ICT diffusion in developing countries including Latin America region, Bakay et al (2010) analysed the ICT readiness levels on socio-economic indicators that might affect ICT either positively or negatively.…”
Section: Review Of Literaturementioning
confidence: 99%